A Postgenomic Body: Histories, Genealogy, Politics. (September 2018) - Meloni, Maurizio
This article sets the stage for a genealogy of the postgenomic body. It starts with the current transformative views of epigenetics and microbiomics to offer a more pluralistic history in which the ethical problem of how to live with a permeable body – that is plasticity as a form of life – is pervasive in traditions pre-dating and coexisting with modern biomedicine (particularly humoralism in its several ramifications). To challenge universalizing narratives, I draw on genealogical method to illuminate the unequal distribution of plasticity across gender and ethnic groups. Finally, after analysing postgenomics as a different thought-style to genomics, I outline some of its implications for notions of plasticity. I argue that postgenomic plasticity is neither a modernistic plasticity of instrumental control of the body nor a postmodernist celebration of endless potentialities. It is instead closer to an alter-modernistic view that disrupts clear boundaries between openness and determination, individual and community.